COMPARATIVE ANALYSIS OF CONSUMER PREFERENCE ON ONLINE NEWS BETWEEN MALE AND FEMALE STUDENT IN MANADO - Nainggolan, Mutiara .; Worang, Frederik G.; Tumiwa, Johan . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The speed of technology has affected some aspects of people’s life, one of which is the need to get quick and accurate information. Internet has become the technology to fulfill people’s need in gaining abundant information. They make Internet as lifestyle tool to be able to access information quickly and accurately from online news services. Consumer Preferences allow a consumer to rank different bundles of goods according to level of utility, or the total satisfaction of consuming a good or service. This research is purposed to analyze the differences of consumer preferences towards online news between male and female students in Manado. This research used the Independent Sample T-Test as the method of this research. Population in this research is the students in Manado. The sample of this research is 100 respondents of random sampling. The comparative analysis of this research is prove that there are significant difference between male and female in order to consume the online news. Male has a higher preference to read the online news rather than the female, when male has higher education and factor situational that can increase their intends of reading the online new.Keywords: marketing, consumer preference, gender, online news